THE SYSTOLIC AND DIASTOLIC BLOOD PRESSURE VALUES IN FEMALE RABBITS WITH METABOLIC SYNDROME (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Objective: This study investigates the systolic and diastolic blood pressure (BP) values in female rabbits with a metabolic syndrome (MS) model. Metabolic syndrome, characterized by a cluster of conditions including hypertension, is a significant risk factor for cardiovascular diseases. Understanding BP changes in an MS model can provide insights into the pathophysiology of hypertension associated with metabolic syndrome. Methods: Female rabbits were induced with metabolic syndrome through a high-fat, high-sucrose diet over a period of 12 weeks. A control group was maintained on a standard diet. Systolic and diastolic BP measurements were taken at baseline and at regular intervals using a non-invasive tail-cuff method. BP values were compared between the control and MS groups, and statistical analysis was performed to assess the significance of observed differences. Results: The MS group exhibited a significant increase in both systolic and diastolic BP values compared to the control group. By the end of the study period, the mean systolic BP in the MS group was notably higher, indicative of sustained hypertension. Similarly, the diastolic BP values were elevated, reflecting increased vascular resistance and potential endothelial dysfunction. These changes were consistent with the development of other metabolic syndrome features such as insulin resistance, hyperlipidemia, and obesity. Conclusion: Female rabbits with an induced metabolic syndrome model showed significant elevations in systolic and diastolic blood pressure, highlighting the hypertensive component of metabolic syndrome. These findings underscore the importance of managing BP in individuals with metabolic syndrome to reduce the risk of cardiovascular complications. Further research is warranted to explore the underlying mechanisms and potential therapeutic interventions to mitigate hypertension in metabolic syndrome.